Corporate Governance Quality and Company Performance - Weli Weli; Rilo Pambudi (Australasian Accounting, Business and Finance Journal, 2023)
The background of this research is to determine the motive associated with the low compliance level of the Financial Services Authority report on the Corporate Governance practices at public companies in Indonesia compared to those in other ASEAN countries. This study aims to analyze the quality disclosure and impact of Good Corporate Governance (GCG) practices by public companies in Indonesia. The differences between this study and the previous are in terms of measuring the assessed GCG quality based on the ASEAN Corporate Governance Scorecard (ACGS) and the five major groups of GCG dimensions. Company performance is measured by accounting and market-based performance, with data collected using the content analysis method. The research object is the annual report and other related reports published in 2017 and 2018 by public companies in the consumer goods industry. The quality of Good Corporate Governance is proportionally calculated by adding the total items disclosed. Data analysis was performed using descriptive analysis and the Mann-Whitney test. The result showed that the disclosure of GCG information by consumer goods industries in Indonesia is low. Furthermore, the relationship between the quality of GCG and company performance has empirical support for market-based performance measures. This study also provides an empirical contribution to research on the implementation of GCG on company performance.
Keywords: corporate governance; CG Quality; disclosure quality; market-based performance; accounting-based performance